2012
DOI: 10.1111/eulj.12015
|View full text |Cite
|
Sign up to set email alerts
|

European Agencies' Rulemaking: Powers, Procedures and Assessment

Abstract: This article aims at identifying European agencies' rulemaking powers, mapping the procedures through which such powers are exercised and assessing the existing procedural arrangements. The first section analyses the main forms of European agencies' rulemaking. It shows, on the one hand, that not all European agencies are actually engaged in the adoption of administrative rules, on the other hand, that European agencies carrying out rulemaking activities tend to converge on two specific forms of rulemaking, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Regulatory rules require interpretations and many ask for modifications once an ERA has gained more experience in implementing the regulatory framework. Within the larger legal framework set by the European institutions, ERAs moreover hold substantive "soft-law" rulemaking competences (Chiti, 2013). By (re-)interpreting and modifying existing rules and introducing new ones, ERAs can effectively raise regulatory standards, for instance by altering the scientific information required for a product authorisation.…”
Section: The Regulatory Framework and Procedural Insulationmentioning
confidence: 99%
“…Regulatory rules require interpretations and many ask for modifications once an ERA has gained more experience in implementing the regulatory framework. Within the larger legal framework set by the European institutions, ERAs moreover hold substantive "soft-law" rulemaking competences (Chiti, 2013). By (re-)interpreting and modifying existing rules and introducing new ones, ERAs can effectively raise regulatory standards, for instance by altering the scientific information required for a product authorisation.…”
Section: The Regulatory Framework and Procedural Insulationmentioning
confidence: 99%
“…In so doing, the attention is paid to a variety of actors and their relative influence. This article argues that the level of pressure coming from external actors, both political and non-political, makes a difference because the legitimate right of EU agencies to contribute to EU decision-making plays the key role in the debates on EU agencies' legal powers (Chiti, 2013;Hofmann & Morini, 2012) and de facto independence (Maggetti, 2012). That is, EU agencies are supposed to be an engine of expertise-based decisions within the EU and to derive their legitimacy by delivering unbiased and well-informed outputs (Borràs, Koutalakis, & Wendler, 2007).…”
Section: Explaining Differences In the Use Of Expertisementioning
confidence: 99%
“…22 This is a problematic practice, since legitimacy requires that regulatory decision-making follows formal rules. 23 In fact, the current procedural framing of soft rule-making is of 'a very ad hoc nature' and resembles a 'patchwork blanket' , where some agencies may have put into place far more sophisticated procedural rules than others.…”
Section: On the Enforceability Of Eu Agencies' Soft Law At The Nationmentioning
confidence: 99%
“…30 Especially in comparison with older agencies, it has been found that the establishing regulations of a number of newer EU agencies proceed in the direction of a proceduralisation of soft law rulemaking. 31 This is particularly the case for the European Supervisory Authorities (ESAs). Their procedures for issuing guidelines and recommendations addressed to national supervisory authorities or financial institutions are provided by their establishing regulations themselves.…”
Section: On the Enforceability Of Eu Agencies' Soft Law At The Nationmentioning
confidence: 99%
See 1 more Smart Citation